PENINGKATAN PRESTASI BELAJAR SISWA MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH PADA MATERI ALAT“ALAT OPTIK DI SMK NEGERI 1 GANDAPURA - Julaidar, Julaidar; Amiruddin, Amiruddin; Salfiyadi, Teuku (JGK (Jurnal Guru Kita), 2022)
Abstract: Improving Student Achievement Through Problem-Based Learning Model on Optical Instrument Material at SMK Negeri 1 Gandapura. This study aims to improve the learning achievement of class X TKJ students through the application of a problem-based learning model on optical instruments material in the Even Semester of the 2021/2022 academic year at SMK Negeri 1 Gandapura. The research subjects were students of Class X TKJ SMK Negeri 1 Gandapura, totaling 21 students in the second semester of the 2021/2022 academic year. This study uses a qualitative approach with the type of classroom action research. The data collected in this study through pre-cycle tests, final tests of each cycle, observation, and interviews. The results of the final test obtained data from the first cycle, students who got a score of 70 only reached 66.66%, and students who scored
Keywords: tasi Belajar; Pembelajaran Berbasis Masalah; Alat-alat Optik